A new microtubule-stabilizing agent shows potent antiviral effects against African swine fever virus with no cytotoxicity - Samvel Sirakanyan; Erik Arabyan; Astghik Hakobyan; Tamara Hakobyan; Garri Chilingaryan; Harutyun Sahakyan; Arsen Sargsyan; Grigor Arakelov; Karen Nazaryan; Roza Izmailyan; Liana Abroyan; Zaven Karalyan; et al. (Emerging Microbes and Infections)
African swine fever virus (ASFV) is the causal agent of a fatal disease of domestic swine for which no effective antiviral drugs are available. Recently, it has been shown that microtubule-targeting agents hamper the infection cycle of different viruses. In this study, we conducted in silico screening against the colchicine binding site (CBS) of tubulin and found three new compounds with anti-ASFV activity. The most promising antiviral compound (6b) reduced ASFV replication in a dose-dependent manner (IC50 = 19.5 μM) with no cellular (CC50 > 500 μM) and animal toxicity (up to 100 mg/kg). Results also revealed that compound 6b interfered with ASFV attachment, internalization and egress, with time-of-addition assays, showing that compound 6b has higher antiviral effects when added within 2–8 h post-infection. This compound significantly inhibited viral DNA replication and disrupted viral protein synthesis. Experiments with ASFV-infected porcine macrophages disclosed that antiviral effects of the compound 6b were similar to its effects in Vero cells. Tubulin polymerization assay and confocal microscopy demonstrated that compound 6b promoted tubulin polymerization, acting as a microtubule-stabilizing, rather than a destabilizing agent in cells. In conclusion, this work emphasizes the idea that microtubules can be targets for drug development against ASFV.